Manfaat Teknologi bagi Mata Pembelajaran PAI di Era Modern - Tarmizi Pane; Anni Saputri Pohan; Gusmaneli Gusmaneli (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The Constitution states that education is an effort to make the nation's life more intelligent and is a continuous teaching and learning activity. And education is also one of the best and most ideal ways to improve the human quality of the world's population. Moreover, Islamic Religious Education. Because, Islamic religious education is a form of education that must be taken by every student in the world, especially those who are Muslim. Therefore, educators must pay more attention to this field of education. The choice of media, strategies, teaching materials and teaching modules is also very important when the learning process takes place. An educator must also be able to use various forms of technology available today. Because, it cannot be denied that students nowadays cannot be separated from technology. The research method used in this research is the literature study method (Bibliography). By turning books, journals and websites regarding Islamic Religious Education and educational technology for PAI learning into secondary data. and the events that the author encountered in the field became the primary data. There are many forms of technology that can be used in the Islamic Religious Education learning process, such as multi-media, internet, Microsoft Office Power Point and various other technologies. From this research it can be concluded that technology plays a very important role in Islamic Religious Education, including one of its roles: explaining concepts that are difficult to understand, showing objects that are too big or too small and so on.